2014
DOI: 10.1155/2014/148248
|View full text |Cite
|
Sign up to set email alerts
|

Solid Waste Management Practices in the Informal Sector of Gweru, Zimbabwe

Abstract: This paper contributes to the debate on the role of the informal sector in solid waste management by examining the effectiveness of informal sector solid waste management practices in transforming waste into nonwaste in the city of Gweru in Zimbabwe. The study focused on 589 informal enterprises that were surveys using questionnaire interviews and focus group discussions with key informants. Analysis of solid waste management in the informal sector of Gweru has revealed that large amounts of waste are generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 12 publications
(18 reference statements)
0
18
0
Order By: Relevance
“…While with no statistical difference between the two groups, 78.6% of the students agreed with the view that the existing method (Donkey pulling trolley) being used by the municipality for solid waste transportation could not cover the whole town [25].…”
Section: Knowledge Of House Hold On Waste Managementmentioning
confidence: 82%
“…While with no statistical difference between the two groups, 78.6% of the students agreed with the view that the existing method (Donkey pulling trolley) being used by the municipality for solid waste transportation could not cover the whole town [25].…”
Section: Knowledge Of House Hold On Waste Managementmentioning
confidence: 82%
“…Arguably, at the heart of the problems of solid waste management are the absence of adequate policies, enabling legislation and an environmentally stimulated and enlightened public. [33][34][35] However, none of these studies went a step further to demonstrate causality between the heavy metals found and human health risks for populations residing near such sites (see online supplementary material, Table 1). …”
Section: Heavy Metals In Waste Disposal Sitesmentioning
confidence: 99%
“…Additionally, the integrated approach to solid waste management (ISWM) is also lacking in Liberia. This serves as a hindrance to tackling MSW management issues because of the lack of strategic planning which is a core element of the Integrated solid waste management approach (ISWM) [40]. One of the many challenges to effectively manage waste in Liberia has been the lack of national commitment and political intent regarding waste management operations.…”
Section: Regulatory and Legislative Frameworkmentioning
confidence: 99%